The role of trust in contract enforcement: An analysis of smallholder farmers and sugar millers in Swaziland - Masuku, Micah B. (International Food Policy Research Institute, 2009)
The purpose of this case study is to investigate the role of trust in a contractual relationship in agricultural commodity markets. This case study was conducted in the sugar supply chain in Swaziland and conceptualizes the supply chain as a series of connected activities concerned with planning, coordinating, and controlling the production of sugar, starting with the production of sugarcane by farmers, through its processing by millers, and finally its sale to consumers. Thus it can be broken into units, beginning with the cane growers who provide sugarcane to millers, who then process it into sugar and pass it on to the Swaziland Sugar Association (SSA), which then markets it on behalf of both farmers and millers.